Role of Estimation of Serum Ferritin, Vitamin B12 and Folic Acid in Management of Beta Thalassemic Children - Singla, Heena; Goyal, Gitanjali (International Journal of Medical Research and Review, 2016)
Objective: To estimate the levels of serum Ferritin, Vitamin B12 and Folic acid in beta thalassemic children. Introduction: Beta thalassemia is the most common genetically transmitted haematological disorder in Indian children. In thalassemia, there is ineffective erythropoiesis which can be either due to excess iron accumulation, or low vitamin B12 and folate status. Study Design: The case-control study was carried out at G.G.S. Medical College and Hospital, Faridkot in department of Biochemistry in collaboration with department of Paediatrics. Materials and methods: In this case-control study, 50 children with with beta thalassemia major in the age group of 4 to 8 years were studied for estimation of serum ferritin, vitamin B12 and folic acid. The control group consisted of 50 age and sex matched healthy children. Results: The study group had much higher serum ferritin levels as compared to healthy controls (p< 0.001). On other hand, the thalassemic children had much lower vitamin B12 level in comparison with healthy controls (p< 0.001). The folic acid levels were also much lower in thalassemic children as compared to healthy controls (p< 0.001). Conclusion: Biochemical screening for levels of serum ferritin, vitamin B12 and folic acid is of paramount importance in management of thalassemic children. Supplementation of vitamin B12 and folic acid could be helpful to improve erythropoiesis in thalassemic children who have proven deficiency of these vitamins, though further studies are needed to establish this hypothesis.